Anatomical considerations for transanal minimal‐invasive surgery: the caudal to cephalic approach. (February 2015) - Aigner, F.; Hörmann, R.; Fritsch, H.; Pratschke, J.; D'Hoore, A.; Brenner, E.; Williams, N.; Biebl, M.; the TAMIS TME Collaboration Group; Weiss, H.; Herbst, F.; Panis, Y.; et al.
Abstract Aim Nerve‐sparing surgery during laparoscopic rectal mobilization is still limited by anatomical constraints such as obesity, the narrowness of the male pelvis, an ultra low rectal cancer or all of these. The transanal approach for total mesorectal excision has overcome the shortcomings of limited access to the rectal 'no‐man's land' close to the pelvic floor. The aim of this anatomical study was to define a roadmap of anatomical landmarks for the caudal to cephalic approach so as to standardize nerve‐sparing rectal mobilization procedures. Method Macroscopic dissections of the pelvis in a caudal to cephalic direction were performed in eight alcohol–glycerol embalmed cadavers. A roadmap of anatomical landmarks was created at different levels of section to demonstrate the sites of nerve injury. Results Extrinsic autonomic nerves to the urogenital organs and the internal sphincter muscle are closely adjacent to the lowest portion of the rectum above the pelvic diaphragm. Conclusion This anatomical guide for the pelvic surgeon should facilitate a safe and nerve‐sparing dissection of the mesorectal plane with a meticulous overview of the lowest autonomic nerve fibres. New anatomical insights by a 'caudal to cephalic' approach to the 'no‐man's land' should help overcome anatomical constraints of a narrow, obese and male pelvis during rectal mobilization procedures.